Classical mechanics - Goldstein, Herbert, 1922-2005 (Addison-Wesley series in physics., 1980)
This classic book enables readers to make connections between classical and modern physics -- an indispensable part of a physicist's education. In this new edition, Beams Medal winner Charles Poole and John Safko have updated the book to include the latest topics, applications, and notation to reflect today's physics curriculum.